Recent Perspectives in Pyrolysis Research 2022
DOI: 10.5772/intechopen.100223
|View full text |Cite
|
Sign up to set email alerts
|

The Biomass Waste Pyrolysis for Biopesticide Application

Abstract: The pyrolysis method has been used in various fields and has attracted the attention of many researchers so that this method can be applied to treat biomass waste. Pyrolysis of biomass occurs through heating a substance with limited oxygen so that the decomposition of complex compounds such as lignocellulose into simpler compounds occurs. The heat energy of the pyrolysis process encourages the oxidation of biomass so that complex carbon molecules break down into carbon and bio-oil. Pyrolysis of biomass for coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The smaller the concentration that can be seen, the better the biosensor features. Limit of Detection (LoD) is the minor analyte concentration that gives a sufficiently large signal and can be distinguished from the signal obtained from the blank with a 99% confidence level [15]. The optimum performance of a biosensor can be determined by its ability to detect the concentration of an analyte.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The smaller the concentration that can be seen, the better the biosensor features. Limit of Detection (LoD) is the minor analyte concentration that gives a sufficiently large signal and can be distinguished from the signal obtained from the blank with a 99% confidence level [15]. The optimum performance of a biosensor can be determined by its ability to detect the concentration of an analyte.…”
Section: Resultsmentioning
confidence: 99%
“…The potentiometer is used as an experimental tool for measuring the potential value of analyte detection [19]. The working electrodes used are Au and a platinum (Pt) as a cathode of the electrolysis process and an Ag/AgCl as a reference electrode.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported the extraction of bioactive compounds from CBS using different techniques, including microwave-assisted extraction (MAE), ohmic heating, deep eutectic solvents, and organic solvents [11][12][13]. However, the use of hydrothermal hydrolysis for this purpose has been scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%